Legal regulation of the Institute of Notary Public in the Kingdom of Serbs, Croats and Slovenes (Kingdom of Yugoslavia) - Drakić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In the Kingdom of Serbs, Croats and Slovenes existed six different legal territories. Due to legal particularism the institute of notary public existed only in those parts of the state that were former Austro-Hungarian territories: Voivodina, Croatia and Slavonia, Slovenia and Dalmatia. In other territories in the common Yugoslav state the institute of notary public was unknown. The basic question regarding the institute of notary public was whether it should be retained in the legal system of Kingdom of Serbs, Croats and Slovenes. After the positive outcome of the survey conducted by the Ministry of Justice, it was decided to adopt a law on notaries, which would apply to the whole state territory. The author in the first part of the paper reviewed the regulations on notary public that were in force in the territory of Voivodina until the adoption of unified law on public notaries. Then the author analyzed the provisions of the Law on Notary Public of Kingdom of Yugoslavia enacted in 1930. However after the adoption of unified Law on Notary Public, it did not enter the force in all parts of the state as it was planed. The issue of justification of the existence of notary public appeared again in the professional public. The lawyers considered that notaries got extended powers and therefore sought to abolish the institution of public notaries. On the other hand the Association of Notaries Public of the Kingdom of Yugoslavia fought for the retention of the institute emphasizing all its advantages.